2013
DOI: 10.1159/000350246
|View full text |Cite
|
Sign up to set email alerts
|

A Novel <b><i>MYO6</i></b> Splice Site Mutation Causes Autosomal Dominant Sensorineural Hearing Loss Type DFNA22 with a Favourable Outcome after Cochlear Implantation

Abstract: Mutations in MYO6 encoding an atypical myosin motor protein important for inner ear hair cell function have been associated with autosomal recessive (DFNB37) and autosomal dominant (DFNA22) types of hearing loss in a few families worldwide. After genome-wide linkage analysis, we identified a novel MYO6 mutation at the splice acceptor site of exon 7 (c.554-1G>A) in an extended German family with autosomal dominant postlingual non-syndromic hearing impairment. Analysis of blood-derived cDNA revealed different ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…χ 2 tests in pairwise comparisons showed no significant differences ( P > 0.1) for all except the Italian family (Melchionda et al., ) in which HL was caused by a missense mutation at the motor domain. Comparison to a recently reported German family (Volk et al., ) is difficult, because only six patients with the most prominent phenotypes were shown. However, the data seemed to suggest that a truncation at the motor domain could lead to early onset ages and severe HL levels.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…χ 2 tests in pairwise comparisons showed no significant differences ( P > 0.1) for all except the Italian family (Melchionda et al., ) in which HL was caused by a missense mutation at the motor domain. Comparison to a recently reported German family (Volk et al., ) is difficult, because only six patients with the most prominent phenotypes were shown. However, the data seemed to suggest that a truncation at the motor domain could lead to early onset ages and severe HL levels.…”
Section: Discussionmentioning
confidence: 80%
“… † The resulting protein change is predicted assuming exon 7 skipping. Volk et al () indeed reported four possible consequences of the splicing change, most of which resulted in frameshift changes starting at p.A185.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been fewer reports on the outcomes for CI for other genes, although some reports have described good performances in CI/EAS patients with associated SLC26A4 ( 25 , 39 ), OTOF ( 25 , 40 , 41 ) , MYO6 ( 8 , 42 ) , MYO15A ( 3 , 4 ) , TECTA ( 3 ) , CDH23 ( 2 ) , COCH ( 5 , 43 ) , MYH9 ( 44 , 45 ), and TMPRSS3 mutations ( 1 , 3 , 6 , 25 , 46 , 47 ). There have also been some reports describing poorer outcomes in patients with POU3F4 mutations, which are known to cause inner ear anomalies ( 48 51 ).…”
Section: Discussionmentioning
confidence: 99%